Inside cyber how AI, 5G, IoT, and quantum computing will transform privacy and our security - Brooks, Chuck (John Wiley & Sons, Inc., 2025)
"In an era where technological innovation evolves at an exponential rate, Inside Cyber: How AI, 5G, and Quantum Computing Will Transform Privacy and Our Security by Chuck Brooks emerges as a critical roadmap for understanding and leveraging the next wave of tech advancements. Brooks, a renowned executive and consultant, breaks down complex technological trends into digestible insights, offering a deep dive into how emerging technologies will shape the future of industry and society"--